Assessment of Ergonomic Strain and Positioning During Bronchoscopic Procedures: A Feasibility Study. Issue 1 (January 2020) - Gilbert, Christopher R.; Thiboutot, Jeffrey; Mallow, Christopher; Chen, Alexander; Pastis, Nicholas J.; Argento, A. Christine; Millar, Jennifer; Lavin, Robert A.; Lerner, Andrew D.; Yu, Diana H.; Salwen, Ben; Lunz, Daniel; et al.
Abstract : Background: Poor ergonomics place health care workers at risk for work-related overuse injuries. Repetitive and prolonged hand maneuvers, such as those performed during endoscopic procedures, may lead to musculoskeletal complaints and work-related injuries. However, the prevalence of health care–related work injuries among physicians is thought to be underreported and there is a paucity of literature investigating the impact of ergonomic strain on bronchoscopy. We designed a feasibility study to explore the differences in ergonomic strain and muscle activity of bronchoscopists. Materials and Methods: A prospective study of bronchoscopic procedures was performed in a simulated environment. Preselected target areas were identified and airway sampling was performed with real-time ergonomic assessment utilizing electromyogram (EMG), grip strength, and musculoskeletal use and motion analysis. Results: Procedural data was obtained for all procedures (78 bronchoscopies by 13 subjects) for both ergonomic and EMG scores. Experienced bronchoscopists demonstrated less EMG burden ( P =0.007) and improved ergonomic positioning ( P =0.007) during bronchoscopy when compared with less experienced bronchoscopists. Procedures performed with rotational-head bronchoscopes trended toward improved ergonomics ( P =0.15) and lower EMG scores ( P =0.88). A significant improvement in ergonomic scores was seen with the rotational-head bronchoscope when targeting the left upper lobe ( P =0.036). Conclusion: Poor ergonomic positioning and excessive muscle strain appear present within bronchoscopy procedures but may be improved in those with more bronchoscopy experience. Technological advances in bronchoscope design may also have the potential to improve procedural ergonomics. Additional prospective studies are warranted to define the long-term impact on bronchoscopic ergonomics. Abstract : Supplemental Digital Content is available in the text.